A Novel Electrochemical Sensor Based on Modified Carbon Paste Electrode with ZnO Nanorods for the Voltammetric Determination of Indole‐3‐acetic Acid in Plant Seed Extracts. Issue 5 (7th January 2022) - Rabie, E. M.; Shamroukh, A. A.; Khodari, M.
Abstract: Detection of indole‐3‐acetic acid (IAA), as a phytohormone, is important for precision farming, plant phenotyping, and crop management. Herein, IAA was detected in bean and wheat plant seeds extractions using zinc oxide nanorods/carbon paste electrode (ZnO NRs/CPE). ZnO NRs/CPE showed excellent electrocatalytic activity, high sensitivity, and selectivity toward the oxidation of IAA. The linearity range was from 30.×10 −8 to 5.0×10 −6 M (r 2 =0.996, n=10), with a detection limit of 1.7×10 −8 M. Moreover, ZnO NRs/CPE exhibited high reproducibility, with a standard deviation of 1.0 % for six successive measurements of IAA. Abstract :